The Growth of Muscle Cell of Inbred Chicken and Indigeneous Chicken Embryo in The Medium of Rabbit Serum and Sheep Serum - Soeroso, JA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
An experiment on the growth embryonic muscle cell in the rabbit and sheep serum media was conducted in the Biotechnology Laboratory of Gadjah Mada University, Yogyakarta. The aim of this experiment was to observe the potency of the growth of embryonic muscle cell of the inbred chicken and indigeneous chicken in the medium of rabbit and sheep serum. Two kinds of embryo, the inbred and indigeneous chicken of eleven days old were used in the experiment. The rabbit and the sheep serum were prepared in the laboratory. The experiment was conducted by applying Nested Classification with basic Complete Randomized Design (CRD). Data collected was analyzed using analysis of variance and also using a proliferation index formula. Samples used in those research were the inner and outer cell nucleus after fourty eight hours of the growth. The result of the experiment indicated that the index of proliferation of embryonic muscle cell of the inbred chicken in the rabbit and sheep serum were 89.65 and 84.92 percent respectively. Whereas, the proliferation index of embryonic muscle cell of the indigeneous chicken in the rabbit and sheep serum were 86.20 and 84.82 percent respectively. The total of inner muscle cell nuclei of inbred chicken embryos was significantly higher (P<0.01) than those of indigeneous chicken embryos either in the rabbit or sheep serum, but there was no difference between the serum (P>0.05). inconclusion the muscle cell of inbred and indigeneous chicken embryos could growth in both serum but the growth muscle cell of inbred chicken embryo was better than that of indigeneous chicken embryo. (Animal Production 2(2): 75-82 (2000)Â Key words : tissue culture, chicken embryos, index proliferation, serum.